On the utility of a mechanistic approach to physiology - the evolutionary origin of endothermy - Torday, John S. (Henry Stewart Talks, 2016)
Evolution of Endothermy, PTHrP, Glucocorticoid and β-Adrenergic Receptor gene duplications, Hypoxia integrates respiratory and endocrine systems, Selection pressure for integrated physiology: lung, kidney, heart, Ontogeny-phylogeny of lung cell evolution, Swim bladder-lung functional homology, PTHrP is stretch-regulated, Chemiosmosis-homeostasis and the origins of life, Vertical integration of the effect of cholesterol on homeostasis, Cell-cell interactions and adaptation to oxygen, Endothermy as exaptation of oxygen adaptation, Physiologic homology based on cell-cell interactions